2006
DOI: 10.1002/dmrr.647
|View full text |Cite
|
Sign up to set email alerts
|

Association of peripheral total and differential leukocyte counts with metabolic syndrome and risk of ischemic cardiovascular diseases in patients with type 2 diabetes mellitus

Abstract: Our results indicate that differential leukocyte counts are associated with MetS and that peripheral leukocytes may play a role in the pathogenesis of macrovascular complications in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 54 publications
2
61
1
1
Order By: Relevance
“…The authors subsequently found that total WBC count was an independent predictor of death/ MI in the patients with or at high risk for CAD, although the most effective risk prediction was observed for the NLR, with the hazard ratio increasing by 2.2-fold for quartile (Q) 4 versus Q1. Thereafter, Tsai J.C. and colleagues studied more than 800 high-risk Korean adult patients (with diabetes mellitus and metabolic syndrome) and determined that NLR was associated with both metabolic syndrome and the risk of ischemic cardiovascular disease 33) . Another prospective study analyzed the predictive ability for cardiac events of the differential WBC count versus was useful, inexpensive and widely available markers of inflammation for predicting the risk and severity of CAD, consistent with the results of our previous study of diabetic patients with stable CAD 17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors subsequently found that total WBC count was an independent predictor of death/ MI in the patients with or at high risk for CAD, although the most effective risk prediction was observed for the NLR, with the hazard ratio increasing by 2.2-fold for quartile (Q) 4 versus Q1. Thereafter, Tsai J.C. and colleagues studied more than 800 high-risk Korean adult patients (with diabetes mellitus and metabolic syndrome) and determined that NLR was associated with both metabolic syndrome and the risk of ischemic cardiovascular disease 33) . Another prospective study analyzed the predictive ability for cardiac events of the differential WBC count versus was useful, inexpensive and widely available markers of inflammation for predicting the risk and severity of CAD, consistent with the results of our previous study of diabetic patients with stable CAD 17) .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that an increased NLR ratio is associated with the incidence of ventricular arrhythmia during PCI 30,31) and a worse outcome after CABG 11) . Moreover, an elevated NLR, both independently and in combination with other disease markers and risk factors, is a significant predictor of the development, progression and mortality of stable CAD 4, 11,23,32,33) . Horne et al MI in patients with stable CAD during a three-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] This finding was found not only in acute conditions but also in stable and preoperative medical conditions. [31][32][33] In a cross-sectional study, Chung et al 34 found a higher neutrophil and lower lymphocyte count in patients with microalbuminuria and overt nephropathy compared with diabetics without albuminuria. Nevertheless, the usefulness of NLR as a predictor of worsening of renal functions among diabetic patients has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Each subtype involved in the inflammatory process in a different way. A number of observational studies have shown a positive correlation between the counts of certain types of leukocytes and the metabolic syndrome or cardiovascular disease (Tsai et al 2007;Kim et al 2008). However, the relationship between specific subtypes of leukocyte and NAFLD has not been studied.…”
mentioning
confidence: 99%